2013
DOI: 10.1002/hyp.9900
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of bacterial contamination in South France coastal rivers: focus on in-stream processes during low flows and floods

Abstract: Abstract:Faecal indicator bacteria (thermotolerant coliform and faecal streptococci) were enumerated in a Mediterranean coastal river to evaluate bacterial contamination levels in relation to hydrological conditions, to estimate delivery of bacterial loads to transitional and coastal waters (Thau lagoon) and to identify bacterial sources of pollution and their contribution to the bacterial flow. Results showed that (1) in low flow conditions, mean bacterial concentrations were higher than EU guidelines for bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 53 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…The observed positive correlation with water temperature does, therefore, not mean that increased temperature leads to the increased E. coli concentrations through bacterial growth. Positive correlation of the E. coli concentration with average water and surface air temperature was in line with other studies (Chu et al, 2013;Medema et al, 1997;Wang and Doyle, 1998). Several authors also provide the coinciding high temperature, precipitation and discharge as main reason for the positive correlation (Koirala et al, 2008;Schilling et al, 2009b) while others link it to bacterial growth (Byappanahalli et al, 2003;Hong et al, 2010;Tiefenthaler et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…The observed positive correlation with water temperature does, therefore, not mean that increased temperature leads to the increased E. coli concentrations through bacterial growth. Positive correlation of the E. coli concentration with average water and surface air temperature was in line with other studies (Chu et al, 2013;Medema et al, 1997;Wang and Doyle, 1998). Several authors also provide the coinciding high temperature, precipitation and discharge as main reason for the positive correlation (Koirala et al, 2008;Schilling et al, 2009b) while others link it to bacterial growth (Byappanahalli et al, 2003;Hong et al, 2010;Tiefenthaler et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…Some authors have observed the spread of contamination in rivers (Chu et al . 2014), and others have proposed models of bacterial mobility in streams (Niu and Phanikumar 2015). Thus, freshwater ecosystems, particularly rivers, are suspected to play an important role in the dispersion of human-associated bacteria into the environment and to serve as reservoirs that can potentially lead to human contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Non-point urban and agricultural land use zones have significant impacts on water quality and produce a large number of fecal bacteria conveyed to water bodies [13,14]. As well, climatic variables like precipitation and wet seasons in a region are suggested to have a positive correlation with the concentration of fecal bacteria in the surface waters [15][16][17].…”
Section: Introductionmentioning
confidence: 99%